Requirements of students for video-annotations in lecture recordings. Issue 3 (9th September 2014) - Markus Ketterl, Dr; Christopher Brooks, Dr; Florian Schimanke, Mr; Rolf, Rüdiger; Reuter, Hannah; Abel, Martin; Hamborg, Kai-Christoph
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Improving the use of annotations in lecture recordings. Design/methodology/approach – Requirements analysis with scenario based design (SBD) on focus groups. Findings – These seven points have been extracted from the feedback of the focus groups: (1) Control of the annotation feature (turn on/turn off). (2) An option to decide who is able to see their comments (groups, lecturer, friends). (3) An easy and paper-like experience in creating a comment. (4) An option to discuss comments. (5) An option to import already existing comments. (6) Color-coding of the different types of comments. (7) An option to print their annotations within the context of the recording. Research limitations/implications – The study was performed to improve the open-source lecture recording system Opencast Matterhorn. Originality/value – Annotations can help to enable the students that use lecture recordings to move from a passive watching to an active viewing and reflecting.